2023
DOI: 10.3390/ijerph20065149
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Family Resilience on the Subjective Well-Being of Offspring in the National Longitudinal Lesbian Family Study

Abstract: The current study used a family resilience approach to investigate why some offspring of sexual minority parents thrive despite homophobic stigmatization while others do not. Specifically, the study explored the role of two specific family functioning mechanisms (i.e., during adolescence, disclosure of offspring’s personal life to their parents, and family compatibility) in the association between experienced homophobic stigmatization at age 17 and subjective well-being at age 25, among 71 offspring (37 female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…We supported how, beyond the gender of the parents and the procreation method, adopting positive parenting strategies, such as being a warm and committed parent, predisposes children to better socio-emotional functioning, leading to the exercise of more prosocial behaviors (e.g., Baiocco et al, 2015 ; Eisner and Malti, 2015 ; Lansford et al, 2021 ). Our findings suggest the relevance of positive parenting practices for understanding subjective well-being and positive behavior development among children, regardless of parents’ gender and sexual orientation ( Bos et al, 2023 ). Overall, societal-level actions (e.g., interventions to promote positive attitudes toward same-gender parent families) can be essential to build a more inclusive and safe society for all family compositions, regardless of parents’ sexual orientation or gender identity ( Patterson, 2009 ).…”
Section: Limitations and Future Directionsmentioning
confidence: 78%
See 1 more Smart Citation
“…We supported how, beyond the gender of the parents and the procreation method, adopting positive parenting strategies, such as being a warm and committed parent, predisposes children to better socio-emotional functioning, leading to the exercise of more prosocial behaviors (e.g., Baiocco et al, 2015 ; Eisner and Malti, 2015 ; Lansford et al, 2021 ). Our findings suggest the relevance of positive parenting practices for understanding subjective well-being and positive behavior development among children, regardless of parents’ gender and sexual orientation ( Bos et al, 2023 ). Overall, societal-level actions (e.g., interventions to promote positive attitudes toward same-gender parent families) can be essential to build a more inclusive and safe society for all family compositions, regardless of parents’ sexual orientation or gender identity ( Patterson, 2009 ).…”
Section: Limitations and Future Directionsmentioning
confidence: 78%
“…Thus, prosocial behaviors can also protect children and adolescents from maladaptive outcomes, such as academic problems, or externalizing behaviors, like verbal or physical aggression, drug use, delinquent conduct, and so on (e.g., Carlo et al, 2011 ). Moreover, prosocial behaviors have recently been conceptualized as the moral manifestation of the positive orientation toward others, encompassing the personality domain of resilience ( Bos et al, 2023 ), so there are shared moral underlying mechanisms for prosociality and externalizing behaviors (e.g., Eisenberg et al, 2015 ; Eisner and Malti, 2015 ). Several previous studies attested that adjustment in children did not vary as a function of the type of couple or the type of conception method because children who lived in different-gender parent families and their same-gender counterparts showed similar levels of well-being, social competencies, and behavioral adaptation (e.g., Colpin and Soenen, 2002 ; Baiocco et al, 2015 ; Bos et al, 2023 ), or, in some cases, children raised by same-gender parents showed better emotional and behavioral adjustment (e.g., Lick et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%